Outbreak of Pneumonic Plague in 2017 on Madagascar - A. Yu. Popova; V. V. Kutyrev; S. A. Shcherbakova; E. B. Ezhlova; Yu. V. Demina; N. D. Pakskina; V. P. Toporkov; N. V. Popov; Ya. V. Sizova; G. A. Eroshenko; S. A. Bugorkova; T. N. Shchukovskaya; et al. (Проблемы особо опасных инфекций, 2017)
The causes of emergence and development of pneumonic plague outbreak in 2017 on Madagascar were analyzed. Summarized were the literature data, characterizing the spatial and biocoenotic structure of natural plague focus on Madagascar, assessed were the risk factors of plague infection among rural and urban population of the island, as well as the properties of Yersinia pestis strains isolated there in the XX century. It is substantiated that the distinctive type of plague outbreaks on Madagascar is a rural one. It is demonstrated that one of the main causes of wide spread of plague in 2017 is importation of the infection from central regions of the Republic of Madagascar into big cities with further formation of multiple epidemic foci. Confirmed was the circulation of Y. pestis strains that belong to the third branch of irradiation of oriental biovar (1.ORI3). Discussed are the issues of diagnostics and treatment of plague in epidemic foci in the territory of the Republic of Madagascar. The evidence is provided to the fact that the plague outbreak in 2017 on Madagascar is the consequence of a lower surveillance level, first and foremost undervaluation of specific and non-specific prophylaxis capacities regarding this infection.